Influence of special physical preparedness of athletes on biomechanical characteristics of performing basic exercises in acrobatic rock'n'roll - Kyzim, P.; Humeniuk, S.; Batieieva, N. (Slobozhanskyi herald of science and sport, 2018)
Purpose: to reveal the effect of special physical preparedness of athletes on the biomechanical characteristics of the performance of the kick-step component of the main course in acrobatic rock'n'roll.